Improving English Basic Skills for YPK Werba Elementary School Students: Upaya Peningkatan Kemampuan Bahasa Inggris Dasar pada Siswa SD YPK Werba - Magfirah, Titing; Ilham, Ilham (Politeknik Negeri Fakfak, 2025)
The Community Service Program that has been carried out is an English language training program for elementary school students of YPK Werba, West Fakfak District, Fakfak Regency. This training program aims to help elementary school students master basic English well. This program also aims to foster students' interest in learning English. And with this effort, it is hoped that students will be able to improve their ability to master basic English, especially in increasing vocabulary. This activity provides training on English vocabulary lessons such as Animals, Body Parts, Fruits, Things in the Classroom, and Short Expressions (greetings and introductions). The training that was carried out was successful. This is evidenced by the enthusiasm of elementary school students to participate in the activity. The results of the questionnaire showed that they really liked this activity and made it easier for them to develop their vocabulary in English (90%). It is hoped that this activity can have a positive impact in the form of increasing the English language skills of the children participating in the training, so that they can later utilize the knowledge and skills in their lives both now and for their future